Penggunaan Sistem Pembayaran QRIS dalam Praktik Pengelolaan Keuangan Mahasiswa Perantauan - Alfian Lutfi; Annisa Ayu Handayani; Balqis Naura Izzati; Khoirunnisa Khoirunnisa; Lutvie Novita Zalwa; Welsi Damayanti (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This study aims to explore the role and impact of the development of digital payment systems, particularly the Quick Response Code Indonesian Standard (QRIS), on the financial management practices of out-of-town students in the 2024 cohort. Using a descriptive qualitative approach and data collected through open-ended questionnaires distributed to 50 students of the Accounting Study Program at UPI, the research examines sources and management of monthly funds, the influence of QRIS on consumptive behavior, the role of QRIS in daily transactions, the handling of unexpected expenses, and students' financial awareness. The results indicate that QRIS is widely used for daily spending transactions, especially for purchasing food and beverages, due to its practicality and convenience. However, the findings also suggest a tendency for increased consumptive behavior among students who use QRIS. Nonetheless, a small portion of students reported that QRIS facilitates easier control over spending through visibility of balances and transaction histories. This study highlights the importance of financial literacy alongside the adoption of digital payment technologies to optimize students' financial management.